Incidence and risk factors for patellofemoral dislocation in adults with Charcot‐Marie‐Tooth disease: An observational study. - Leone, Enza; Davenport, Sally; Robertson, Claire; Laurà, Matilde; Skorupinska, Mariola; Reilly, Mary M.; Ramdharry, Gita (Physiotherapy Research International, 2023)
Background and Purpose: Patellofemoral (PF) dislocation is frequently encountered in clinical practice among people with Charcot‐Marie‐Tooth disease (CMT), but the frequency and risk factors for PF dislocation in adults with CMT are unknown. This study aimed to establish the incidence of PF dislocation in adults with CMT and to explore the risk factors associated with PF dislocation. Methods: This is a cross‐sectional study involving adults with a diagnosis of CMT, attending their outpatient clinics at a specialist neuromuscular centre in the United Kingdom. Eighty‐one individuals were interviewed about any PF dislocation and underwent a lower‐limb assessment, with a focussed knee examination, to identify possible risk factors for PF dislocation. The incidence of PF dislocation was expressed as a percentage (number of individuals with a positive history of patellar dislocation/overall sample) and the association between different risk factors and PF dislocation was explored using logistic regression analysis. Results: The incidence of PF dislocation was 22.2% (18/81). PF dislocation was associated with a younger age at the time of the assessment (p = 0.038) and earlier disease onset (p = 0.025). All people bar two who dislocated had CMT1A (88.9%), but there was no difference in terms of CMT distribution with the non‐dislocation group (p = 0.101). No association was found between PF dislocation and CMT severity measured by CMTSS (p = 0.379) and CMTES (p = 0.534). Patella alta (p = 0.0001), J‐sign (p = 0.004), lateral patellar glide (p = 0.0001), generalised joint hypermobility (p = 0.001) and knee flexors weakness (p = 0.008) were associated with an increased risk of dislocation. Patella alta (p = 0.010) and lateral patellar glide (p = 0.028) were independent PF dislocation predictors. Conclusions: PF dislocation was common in this cohort with CMT and was associated with multiple risk factors. Future studies should be conducted to confirm the present findings so that the identified risk factors may be addressed by clinicians through preventive, supportive and corrective measures.